Studies on Extraction Resistance of Hydroxyl Terminated Polybutadiene Bound 2,2-Thiobis(4-methyl-6-tert-butylphenol) in Natural Rubber Vulcanizates - Wang, Yonghong; Zeng, Xingrong; Li, Hongqiang; Guo, Jianhua (Asian Journal of Chemistry, 2012)
A novel polymeric anioxidant, hydroxyl terminated polybutadiene bound 2,2-thiobis-(4- methyl-6-tert-butylphenol) (HTPB-IPDI-TPH) with excellent thermo-oxidative aging resistance, was synthesized from hydroxyl terminated polybutadiene (HTPB), 2,2-thiobis-(4-methyl-6-tert-butylphenol) (TPH) and isophorone diisocyanate (IPDI). The extraction resistance of HTPB-IPDI-TPH in natural rubber vulcanizates was studied by thermo-oxidative aging resistance of natural rubber vulcanizates after methanol and water extraction. The results showed that HTPB-IPDI-TPH had less extraction than conventional sterically hindered phenol antioxidant 2,2-thiobis-(4-methyl-6-tert-butylphenol) and had remarkable effect on the thermo-oxidative aging resistance for natural rubber vulcanizates of methanol extraction in the later stage of aging.